Teknologi Blockchain berbasis Non Fungible Token sebagai Penghargaan Partisipasi Donor Darah - Moleo, Alif Safa; Hasanuddin, Tasrif; Darwis, Herdianti; Harlinda, Harlinda (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Non-fungible tokens (NFTs) are a technological innovation that has been widely used to provide a form of digital reward. However, the application of NFTs in the social domain, especially in blood donation programs, has not been widely explored. This research aims to develop an NFT-based reward system using blockchain technology as an appreciation for blood donors. The system is designed and developed using the Ethereum test network due to its stability in decentralized applications. This research uses the research and development (R&D) method with the 4D model approach, which consists of the Define, Design, Develop, and Disseminate stages. In the Define stage, a needs analysis was conducted to determine the system specifications. The Design stage involves the design of a web-based system3 to support NFT management. In the Develop stage, the system was developed using the Ethereum testing network. The Disseminate stage includes system testing using the black box method to ensure that all key features, such as NFT claims and data transparency, function properly. The result of the research is an NFT-based blockchain application that allows blood donors to easily claim their NFTs as a form of digital recognition. The evaluation showed an acceptability score of 61.34%, indicating that this application is acceptable to the community and has the potential to increase blood donor motivation. The implementation of this system is expected to have a sustainable positive impact on increasing blood donor participation in the future.